Structural and Optical Properties of Nanoparticle ZnO Deposited by Spray Pyrolysis - Bakha, Y.; Khales, H.; Serhane , R.; Smatti, A. (Algerian Journal of Research and Technology (AJRT), 2018)
We present in this paper the deposition of nanoparticle zinc oxide (ZnO) by a simplified chemical spray process. A deposition was carried on glass substrates at different temperatures, to determine the ZnO optimal parameters. The characterization results by X-ray diffraction (XRD), scanning electron microscopy (SEM) and transmittance, shows that the obtained thin films are in good agreement with the reported ZnO properties. The films exhibit a hexagonal wurtzite structures. Scanning electron microscopy (SEM) measurements showed that the surface morphology of the films changed with temperature deposition. The studies demonstrated that the ZnO film had a transmission of about 85% and energy gap of 3.2eV to 3.3eV with increasing temperatures from 300°C to 350°C. The optical band gap of deposited films at temperatures of 400°C to 500°C increased from 3.56eV to 3.76eV.